Fantastic 4. Rise of the Silver Surfer - Story, Tim.; Gruffudd, Ioan.; Alba, Jessica, 1981-; Evans, Chris, 1981-; Chiklis, Michael, 1963-; McMahon, Julian, 1968-; Washington, Kerry, 1977-; Braugher, Andre; Jones, Doug, 1960-; Fishburne, Laurence, III, 1961-; Twentieth Century-Fox Film Corporation; Constantin Film (Firm); et al. (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2007)
When the Silver Surfer arrives on Earth, army General Hager demands that Reed Richards create a sensor to track him and find out what he's doing on Earth. The only problem is that Richards is helping Sue Storm plan their rescheduled wedding. Ben Grimm is heating up his relationship with Alicia and Johnny Storm is trying to get sponsorships and girls. Returning is Victor Von Doom, who gladly offers to assist the military in figuring out what the Silver Surfer is all about.
English track: Dolby digital 5.1.
Spanish and French tracks: Dolby digital surround.
Title from container.
Based on the characters created by Stan Lee and Jack Kirby.
Special features: Side A: Full screen version; commentary by Tim Story; commentary by Tim Story, Ioan Gruffudd, Jessica Alba, Chris Evans, Michael Chiklis, Doug Jones and Julian McMahon; commentary by Kevin Feige, Michael France, Ralph Winter, Mark Frost and Don Payne. Side B: Widescreen version; commentary by Tim Story; commentary by Tim Story, Ioan Gruffudd, Jessica Alba, Chris Evans, Michael Chiklis, Doug Jones and Julian McMahon; commentary by Kevin Feige, Michael France, Ralph Winter, Mark Frost and Don Payne.
Director of photography, Larry Blanford ; editors, Peter S. Elliot, William Hoy, Michael McCusker ; music, John Ottman ; costume designer, Mary E. Vogt ; production designer, Kirk M. Petruccelli.
Keywords: Silver Surfer -- (Fictitious character) -- Drama; Fantastic Four (Fictitious characters) -- Drama; Detectors -- Drama; Weddings -- Drama; Criminal behavior -- Drama; Video recordings for the hearing impaired; Feature films; Science fiction films; Fantasy films; Action and adventure films